A Phenomenological Exploration of Tattooing:: A Personal and Meaning-filled Experience - Adamson, Alex (European Journal for Qualitative Research in Psychotherapy, 2011)
This paper explores the personal and meaning-filled experience of what one woman’s tattoos subjec- tively mean to her in the context of her life. Merging a dialogical-relational Gestalt theoretical base with a relational-hermeneutic phenomenological approach, I collected data by interviewing my participant in a 45 minute open-ended depth interview exploring her life experience. Analysis based on iterative re- readings of the transcript drew on narrative, reflexive and creative metaphorical forms. Findings reveal that my participant’s experience of her tattoos seems to link - in simple but profound ways - with grief. Having been confronted by the ending of two of the biggest relationships with males (her father and ex-husband), she made the somewhat unconscious choice to mark the transitioning between the roles of daughter and ex-wife and reclaim her own sense of skin. Her tatoos of two lizards seem to symbolise and represent her African home, sexuality, resourcefulness, survival and ultimately a reclaiming of her own self.